VALIDASI METODE ANALISA KADAR FENOLIK EKSTRAK ETANOL PATIKAN KEBO (Euphorbia hirta L) DENGAN MENGGUNAKAN SPECTROSCOPY UV- VIS - Sari, Mesi Puspita (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Validation research has been carried out on the phenolic content analysis method using the DPPH method on the ethanol extract of Patikan Kebo. In this research, the patikan kebo leaves were previously characterized microscopically and macroscopically and a phytochemical screening test was carried out to determine the secondary metabolite content in the patikan kebo leaves. Next, extraction is carried out using the maceration method. The resulting extract is then analyzed to determine the phenolic content in the sample. Determination of phenolic content uses a method that is first calibrated, which includes linearity, LOD and LOQ, precision, accuracy and sensitivity. The results of each analytical parameter analysis are as follows: linearity = 0.9909, precision = 0.046; 0.06; 0.019 recovery = 98 and 102 %, sensitivity = 1.02. 105 L. Mol-1 cm-1. Analysis of the phenolic sample showed a concentration value of 36.3 mg GAE/gram of patikan kebo extract.